The Importance of Glycans of Viral and Host Proteins in Enveloped Virus Infection - Li, Yuqing; Liu, Dongqi; Wang, Yating; Su, Wenquan; Liu, Gang; Dong, Weijie (Frontiers in Immunology, 2021)
Animal viruses are parasites of animal cells that have characteristics such as heredity and replication. Viruses can be divided into non-enveloped and enveloped viruses if a lipid bilayer membrane surrounds them or not. All the membrane proteins of enveloped viruses that function in attachment to target cells or membrane fusion are modified by glycosylation. Glycosylation is one of the most common post-translational modifications of proteins and plays an important role in many biological behaviors, such as protein folding and stabilization, virus attachment to target cell receptors and inhibition of antibody neutralization. Glycans of the host receptors can also regulate the attachment of the viruses and then influence the virus entry. With the development of glycosylation research technology, the research and development of novel virus vaccines and antiviral drugs based on glycan have received increasing attention. Here, we review the effects of the host glycans and viral proteins on biological behavior of viruses, and the opportunities for prevention and treatment of viral infectious diseases.